Розв’язання задач інтерполяції у CAD-системі solidworks - Гавриленко, Євген Андрійович; Михайленко, Олена Юріївна; Havrylenko, Yevhen; Mykhailenko, Olena (Запоріжжя : Видавничій дім "Гельветика", 2025)
UA: У роботі досліджуються можливості CAD-системи SolidWorks з моделювання гладких обводів із регулярною зміною кривини. Запропоновано методику формування обводів дугами еліпсів і В-сплайнів, що забезпечує інтерполяцію будь-якого точкового ряду по частинах, які можна інтерполювати монотонною кривою лінією. Обвід формується всередині області можливого розташування опуклої кривої лінії, якою можна інтерполювати точковий ряд. Можливості розроблених способів підтверджено розв’язанням задач інтерполяції послідовності точок, які призначені на монотонних кривих лініях. Задачі розв’язані в CAD системі SolidWorks за допомогою програми, створеної на основі розроблених у роботі способів. /// EN: The paper examines the capabilities of a CAD system for solving interpolation problems. The problem of modelling a smooth contour with a regular change in curvature representing a monotone curve with specified accuracy is solved in the article. The contour is formed within the area of possible location of a convex curve, which can interpolate a point series. The assumption that if a sequence of points can be interpolated by a monotone curve, the original curve on which these points have been assigned is monotone, allows to use the proposed approach to estimate interpolation error of a point series of arbitrary configuration. The proposed methods for forming a convex regular contour by arcs of ellipses and B-spline ensure interpolation of any point series in parts that can be interpolated by a monotone curve. At the same time, deviation of the contour from the boundaries of the area of possible location of the monotone curve is controlled. The study demonstrates that it is possible to achieve an arbitrarily small interpolation error by decreasing the distances between initial points on a monotonic curve by increasing their number. The sequence of interpolated points can be increased both by refining the initial data and by assigning intermediate points. The possibilities of the developed methods are tested while solving problems of interpolation of a point series belonging to monotone curves. The problems are solved in the CAD system SolidWorks with the use of software application created on the basis of the methods developed in the research work. The developed methods are appropriate for use in modeling linear elements of the framework of functional surfaces with enhanced aerodynamic and hydrodynamic properties, for which the minimum number of singular points is the main criterion for the quality of the resulting solution.
Solving interpolation problems in the solidworks CAD-system
Keywords: інтерполяція; дотична пряма; кривина; область розташування кривої; обвід; похибка; CAD-система; програмний додаток; interpolation; tangent line; curvature; area of location of the curve; contour; error; CAD-system; software application